Do Muslim households with above-average levels of education give more to alms? - Pricilia Devani; Alfiah Hasanah (Universitas Airlangga, 2023)
ABSTRACT The aim of this study was to examine the effect of above-average educational attainment of Muslim households on the amount of alms given by the household. This study uses panel data from the Indonesian Family Life Survey Wave 4 and Wave 5, with a sample consisting of Muslim household heads with a history of secondary education (SMA/SMK) and higher education. The data were processed and analysed using the fixed effects regression method using STATA software version 17. The results of this study indicate a significant and positive influence between the above-average level of education of Muslim households and the amount of charitable expenditure of the household. A household headed by a person with a high school, vocational school, or university education is predisposed to a higher amount of alms giving. Individual characteristics of the household head, including marital status, occupation, and religious observance, play a significant role in determining the amount of household alms given. This research has potential implications for providing recommendations to the community, religious institutions, and the government to increase participation and the amount of alms given. Keywords: household alms, secondary education, higher education, IFLS, fixed effect ABSTRAK Tujuan dari penelitian ini adalah untuk menyelidiki pengaruh tingkat pendidikan rumah tangga muslim di atas rata-rata terhadap jumlah pengeluaran sedekah rumah tangga. Penelitian ini menggunakan data panel yang bersumber dari data Indonesian Family Life Survey gelombang 4 dan gelombang 5, dengan sampel yang terdiri atas kepala rumah tangga beragama Islam dan memiliki riwayat pendidikan menengah (SMA/SMK) dan Perguruan Tinggi. Data tersebut diolah dan dianalisis menggunakan metode regresi Fixed Effect dengan bantuan software STATA versi 17. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan dan positif antara tingkat pendidikan rumah tangga muslim di atas rata-rata dengan jumlah pengeluaran sedekah rumah tangga. Rumah tangga dengan kepala rumah tangga dengan riwayat pendidikan pada tingkat SMA/SMK dan Perguruan Tinggi cenderung memberikan jumlah sedekah yang lebih besar. Selain tingkat pendidikan, karakteristik individu kepala rumah tangga seperti status perkawinan, pekerjaan, dan kepatuhan beribadah menjadi faktor yang cukup penting dalam memengaruhi besaran sedekah rumah tangga yang diberikan. Penelitian ini dapat berimplikasi sebagai dasar untuk memberikan rekomendasi kepada masyarakat, lembaga agama, dan pemerintah dalam upaya meningkatkan partisipasi dan jumlah sedekah. Kata Kunci: Sedekah Rumah Tangga, Pendidikan Menengah, Perguruan Tinggi, IFLS, Fixed Effect